Pathological Findings in Male Patients With Anti-N-methyl-d-Aspartate Receptor Encephalitis. Issue 8 (31st May 2019) - Hirano, Makito; Itoh, Tatsuki; Fujimura, Harutoshi; Inoue, Kimiko; Samukawa, Makoto; Nose, Kazuhiro; Sakamoto, Hikaru; Maekura, Shunji; Ueno, Shuichi; Satou, Takao; Nishioka, Tsukasa; Kusunoki, Susumu; et al.
Abstract: Anti-N-methyl-d -aspartate receptor (anti-NMDAR) encephalitis is the most common type of autoimmune encephalitis. The disease predominantly affects women (1:5–1:10), with only 3 reports of autopsy findings in women being published to date. The present study reports findings from the first autopsy performed on a man with anti-NMDAR encephalitis. The patient had some scattered lesions in the limbic system with neuronal loss, gliosis, and microglial activation. The temporal and frontal cortices showed additional patchy demyelination. T-lymphocyte infiltration was detectable in the fusiform gyrus lesion. These findings were partly similar to those reported in female patients. Although clinical differences based on the sex of the patient are reported for this disease, the observed pathological similarities potentially help to establish common therapeutic strategies for all patients. Severe testicular damage was additionally observed in the male patient in this study. Biopsy-proven severe testicular damage was also confirmed in another, previously fertile man who became azoospermic. Moreover, serum follicle-stimulating hormone levels, which often increased in response to disturbed spermatogenesis, were elevated, and testosterone/luteinizing hormone ratio reflecting Leydig cell function was low in all 5 male patients in this study. Overall, these findings suggest similar brain pathology in patients of both sexes and severe testicular damage in male patients.